Golden cables of sympathy : the transatlantic sources of nineteenth-century feminism - McFadden, Margaret (The University Press of Kentucky, 2009)
An intricate network of contacts developed among women in Europe and North America over the course of the nineteenth century. These women created virtual communities through communication, support, and a shared ideology. Forged across boundaries of nationality, language, ethnic origin, and even class, these connections laid the foundation for the 1888 International Council of Women and formed the beginnings of an international women's movement. This matrix extended throughout England and the Continent and included Scandinavia and Finland. In a remarkable display of investigative research, Marg.